The demon's daughter : a love story from South India - Piṅgaḷi Sūrana (SUNY series in Hindu studies., 2006)
"The Demon's Daughter (Prabhavati-pradyumnamu) is a sixteenth-century novel by the south Indian poet Pingali Suranna, originally written in Telugu, the language of present-day Andhra Pradesh. Suranna begins with a story from classical Hindu mythology in which a demon plans to overthrow the gods. Krishna's son Pradyumna is sent to foil the plot and must infiltrate the impregnable city of the demons; Krishna helps ensure his success by having a matchmaking goose cause Pradyumna to fall in love with the demon's daughter. The original story focuses on the ongoing war between gods and anti-gods, but Pingali Suranna makes it an exploration of the experience of being and falling in love. In this, the work evinces a modern sensibility, showing love as both an individualized emotion and the fullest realization of a person, transcending social and cultural barriers." "The translators include an afterword that explores the cultural setting of the work and its historical and literary contexts. Anyone interested in the literature and mythology of India will find this book compelling, but all readers who love a good story will enjoy this book. Velcheru Narayana Rao and David Shulman have provided a translation that will serve well the contemporary reader who wishes to encounter a masterwork of world literature largely unknown in the West."--Jacket